Exercise training: which impact on COPD patients? - Djebaili, R. (International Journal of Medicine, 2024)
Introduction: Exercise training reactivates the aerobic pathway through physical exercise, thereby improving dyspnea and breaking deconditioning spiral in chronic obstructive pulmonary disease (COPD) patients.Method: 60 COPD patients were selected to benefit from a four-week outpatient exercise training and muscle strengthening program, at a rate of 3 sessions per week, after excluding the following cases: patients who have contraindications to exercise training; severe patients or those receiving long-term oxygen therapy. The program combined exercise training on a bicycle ergometer for 45 min, muscle strengthening of the lower limbs and nutritional monitoring. Nutritional management included a diet based on nutritional status and the prescription of oral food supplements for malnourished COPD patients. Parameters assessed before and after training were bioimpedance analysis (BIA),6MWT, quadriceps isometric voluntary contraction (MVC) and dynamic endurance, and the quality-of-life questionnaire (Q11).Result: Forty COPD patients (36 men and 4 women) aged 67.22 (± 10) years were able to complete the program. Amid them, 36 were non-smokers. Ten patients (GOLD I), 14 patients (GOLD II), 16 patients (GOLD III), no patients (GOLD IV). Dyspnea was stage 2 (± 1) m MRC. After training, quadriceps muscle function ((MVC) and endurance) improved significantly (p < 0.0001). The improvement in distance covered during 6MWT was also significant (p < 0.0001). A significant improvement in quality of life after training was noted on the total score of the Q11 questionnaire. No significant improvement in body composition after training in COPD patients.Conclusion: this study has confirmed the beneficial effects of training mainly on muscle function, effort capacity and quality of life in COPD patients.